EXTENSION OF MICROINSTRUCTION FORMAT IN COMPOSITIONAL MICROPROGRAM CON TROL UNIT WITH ELEMENTARIZATION OF OPERATIONAL LINEAR CHAINS - Barkalov, A. A.; Zelenyova, I. Y.; Miroshkin, A. N. (Radio Electronics, Computer Science, Control, 2011)
Анотація